Effect of Phase Feeding Supplemental Fungus Myceliated Grain on Oocyst Excretion and Performance of Broiler Chickens - Willis, W.L.; Isikhuemhen, O.S.; Hurley, S.; Ohimain, E.I. (International Journal of Poultry Science, 2010)
An experiment was conducted to investigate Fungus Myceliated Grain (FMG) feed inclusion strategies for broilers and the effects of this feed on natural Eimeria oocyst excretion and bird performance. Two hundred ninety-four straight-run day-of-hatch broiler chicks were obtained from a local commercial hatchery and randomly distributed in seven treatment groups with three replications of 14 chicks as follows: 1) Control-No FMG; 2) 5% FMG-starter feed; 3) 5% FMG-grower feed; 4) 5% FMG-starter, grower, finisher feed; 5) 10% FMG-starter feed; 6) 10% FMG-grower feed and 7) 10% FMG starter, grower, finisher feed. Fecal oocyst count, mortality, live body and bursa weight were determined at the end of the 7 wk trial. Results showed that broilers in treatments 1 and 2 produced the highest counts of Eimeria, which was significantly higher than that of treatment 6 (p